KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN KOMUNIKASI ORGANISASI PENGARUHNYA TERHADAP KOMITMEN ORGANISASI GURU - Zainuddin Zainuddin; Badrudin Badrudin; Erni Haryanti (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
This study was conducted to reveal the principal's transformational leadership and organizational communication its effect on teacher organizational commitment. This study uses a quantitative approach with a survey method with a total sample of 28 teachers. The data collection technique used a questionnaire with a Likert scale. Data were analyzed using simple and multiple correlation and regression techniques. The results of this study indicate that the principal's transformational leadership and organizational communication have a joint effect on the variable of teacher organizational commitment by 92.2% which means very strong. So it can be concluded that the better the principal's transformational leadership and organizational communication, the better the teacher's organizational commitment.